Importance of a conserved TCR J alpha-encoded tyrosine for T cell recognition of an HLA B27/peptide complex. - Bowness, P; Allen, R; Barclay, D; Jones, E; Mcmichael, A (1998)
Human HLA B27-restricted cytotoxic T lymphocytes (CTL) specific for the influenza A epitope NP383-391 use similar TCR alpha and beta chains, with two closely related J alpha segments used by six of nine CTL clones from three unrelated donors (Bowness et al., Eur J. Immunol. 1993. 23: 1417-1421). The role of TCR complementarity-determining region (CDR)3alpha residues 93 and 100-102 was examined by site-directed mutagenesis, following expression of the TCR alpha and beta extracellular domains from one clone as a TCR zeta fusion heterodimer in rat basophil leukemia (RBL) cells. For the first time we have measured direct binding of tetrameric HLA B*2705/NP383-391 complexes to transfected TCR. Independently peptide-pulsed antigen-presenting cells (APC) were used to induce TCR-mediated degranulation of RBL transfectants. Our results show a key role for the conserved TCRalpha CDR3 J alpha-encoded residue Y102 in recognition of HLA B27/NP383-391. Thus the Y102D mutation abolished both tetramer binding and degranulation in the presence of peptide-pulsed APC. Even the Y102F mutation, differing only by a single hydroxyl group from the native TCR, abolished detectable degranulation. Further mutations F93A and S100R also abolished recognition. Interestingly, the N101A mutation recognized HLA B27/NP in functional assays despite having significantly reduced tetramer binding, a finding consistent with "kinetic editing" models of T cell activation. Modeling of the GRb TCR CDR3alpha loop suggests that residue Y102 contacts the HLA B*2705 alpha1 helix. It is thus possible that selection of germ-line TCRAJ-encoded residues at position 102 may be MHC driven.